Measurement of wiener spectrum of radiographic screen-film systems - Wan Hassan, Wan Muhamad Saridan (Penerbit UTM Press, 2001)
A method to measure the Wiener spectrum of radiographic screen-film systems in a hospital setting is presented. Radiographs exposed to uniform X-rays are scanned by a microdensitometer, and optical density fluctuation data about the mean density are obtained by subtracting the mean density from the density values. The data are low-pass-filtered by averaging pairs of pixels, followed by low-frequency filtering to eliminate very low-frequency components. A slit trace is synthesised by averaging adjacent traces and the trace is segmented to segments of 256 data points per segment with overlap of 128 data points. Data in each segment are windowed and fast Fourier transformed. The Fourier coefficients are squared and normalized to obtain the power spectrum. On site measurement for Lanex Regular and Lanex Fine screens gives results that are comparable with published data.